Evaluating the integration hypothesis: A meta‐analysis of the ICSEY project data using two new methods. - Abu‐Rayya, Hisham M.; Berry, John W.; Sam, David L.; Grigoryev, Dmitry (British Journal of Psychology, 2023)
The Integration Hypothesis states that acculturating migrants who adopt the integration strategy (i.e. being doubly engaged, in both their heritage culture and in the larger national society) will have better psychological and socio‐cultural adaptation than those who adopt any other strategy (Assimilation, Separation or Marginalization). This hypothesis was supported in the original evaluation of the ICSEY project data, using the mean adaptation scores for individuals in the four acculturation clusters. This conclusion was further supported by an analysis that used scores that were derived from the two underlying dimensions. This paper further evaluates this hypothesis meta‐analytically using two new methods: Cultural Involvement and Cultural Preference; and Euclidean Distance. The results showed that these two methods provided support for the integration hypothesis, for both psychological adaptation and socio‐cultural adaptation. The pattern of relationships was stronger for positive than for negative indicators of adaptation. Theoretical and practical implications of the results are discussed.